Police, Institutional Communication, and Social Media Pressure: A Socio-Legal Study of Institutional Responses to Viral Cases in the Digital Age - Idris Sandiya; Solikhah Yuliatiningtyas; A. Hanief Saha Ghafur (Universitas Negeri Semarang, 2026)
This study investigates how the Indonesian National Police (Polri) constructs its institutional communication in response to social media pressure during viral legal controversies, and how such responses affect police legitimacy in the digital age. Anchored in a socio-legal framework and employing Fairclough’s Critical Discourse Analysis, the research focuses on a high-profile criminal case that triggered national outrage and sustained digital activism, without explicitly naming the case to preserve analytical generality. The analysis examines the use of formal diction, labeling strategies, language modality, and delegitimization of public criticism within Polri’s official communications. Data sources include press statements, social media content by the Police Public Relations Division, official remarks quoted in mainstream media, and related institutional documents. Findings reveal that viral public discourse exerts significant influence on institutional actions—such as forming special investigative teams and dismissing senior officials—highlighting the role of digital pressure in prompting accountability. However, the study also uncovers the temporary and reactive nature of these responses, particularly when public attention fades. By connecting institutional communication strategies with public expectations in digital spaces, this study argues that the legitimacy of law enforcement is increasingly shaped by the ability to engage transparently and consistently with the public—not merely by legal authority. Viral cases thus function as informal mechanisms of oversight. This research contributes to socio-legal scholarship by integrating insights from democratic policing, digital activism, and public accountability, offering a conceptual lens to understand the dynamic interplay between state institutions and digital society in contemporary Indonesia.